Using blended Teaching in Teaching Mathematics in the Second Cycle in the Sultanate of Oman: The Perception of Teachers in Al-Dakhiliyah Governorate - Al-khusaibi, Mahmood Hamed Saed; Al-Riyami, Mohammed Nassir Saif (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to investigate the reality of using blended teaching in teaching mathematics in the second cycle in the Sultanate of Oman from the perspective of teachers in Al-Dakhiliyah Governorate schools. Depending on the descriptive approach, the researcher used a questionnaire as a research tool, and he chose a sample of 105 teachers, and he used (SPSS) to analyze the collected data. The results of the study showed that the degree of using blended teaching in teaching mathematics in the second cycle in Al-Dakhiliyah Governorate schools was medium. There was a high degree of agreement in regard to “the degree of availability of educational technologies”, a medium degree of agreement in "the importance of using blended education in teaching mathematics" and a low degree of agreement in both "the degree of using blended teaching in mathematics classes" and "the obstacles of using blended teaching in mathematics classes. The results also showed no significant differences in the responses regarding “using blended teaching” and “the obstacles of using blended teaching” according to the variables of gender and years of experience except in "the availability of educational techniques" where there were significant differences in the responses according to the variable of gender for females. The study recommends training and guiding teachers on using the available technologies in schools in the blended teaching process and implementing different teaching methods that encourage the use of blended teaching in the colleges of education in higher education institutions.